Pathogenesis and clinical features of congenital stationary night blindness in case of c.283delC NYX gene mutation - M. E. Ivanova; K. V. Gorgisheli; I. V. Zolnikova; D. S. Atarshchikov; D. Barh; Zh. M. Salmasi; L. M. Balashova (Российский офтальмологический журнал, 2019)
The complete form of X-linked congenital stationary night blindness (CSNB) is a rare genetic disease caused by a mutation in the NYX gene. CSNB is associated with the mutations taking place in 17 genes, whilst its CSNB1A form is caused by the mutations in the NYX gene, which were characterized earlier, although nothing had been reported so far about the Russian founder principle. The paper analyzes the pathogenetic mechanisms in a family with diagnosed CSNB1A and a new genetically confirmed mutation in the NYX gene in four members of one Russian family. Two brothers of the four siblings (two boys, two girls) with congenital stationary night blindness, diagnosed in early childhood, and high myopia underwent a standard ophthalmic examination, supplemented with OCT, electroretinography and color blind test with tables by Rabkin and Farnsworth test, whereupon they were sent to molecular genetics confirmation of the diagnosis by whole exome sequencing with subsequent Sanger sequencing confirmation of the detected mutation in the proband and proband’s relatives. In members of the family with clinical features of CSNB1A the reading frame shift mutation was genetically confirmed in the NYX gene (c.283delC, p.His95fs, NM_022567.2). This mutation is inherited in X-linked form. This is the first report of a case with a novel and probable founder mutation from Russia associated with CSNB1A. Since the mRNA of a NYX gene consists of only 2696 base pairs, a gene replacement therapy, or CRISPR-based gene editing, or a similar approach may be envisaged for the correction of frameshift in His95fs position.